The addition of rosehip oil to Aloe gels improves their properties as postharvest coatings for maintaining quality in plum. (15th February 2017) - Martínez-Romero, Domingo; Zapata, Pedro J.; Guillén, Fabián; Paladines, Diego; Castillo, Salvador; Valero, Daniel; Serrano, María
Highlights: The addition of RO to AV and AA gels maintains quality of President plum. Shelf life of plums was extended with enhanced bioactive compounds. The addition of RO to AV and AA gels reduced plum metabolism. Abstract: The effect of Aloe vera gel (AV) and Aloe arborescens gel (AA) alone or in combination with rosehip oil (RO) at 2% on ethylene production, respiration rate, quality parameters, bioactive compounds and antioxidant activity during plum postharvest storage was studied. Coated plums showed a delay in ethylene production and respiration rate at 20 °C and during cold storage and subsequent shelf life, the main effect being observed for those fruits coated with AA + RO. Quality parameters such as softening, colour and maturity index was also delayed during storage by the use of the coatings, which led to a 2-fold increase in plum storability. Accumulation of bioactive compounds was also delayed although at the end of the experiment the content of bioactive compounds was higher than those found for control fruits at the estimated shelf life. The most effective coating for maintaining plum quality and bioactive compounds was AA + RO.